Roteamento multicamada baseado em eficiência energética e qualidade de enlace para redes de sensores sem fio - MACHADO, Kássio Leonardo da Silva (Universidade Federal do Pará, 2014)
Multilayer routing based on energy efficiency and link quality for wireless sensor networks This Thesis describes the development of a new routing protocol for Wireless Sensor Networks (WSN) for energy restriction and scenarios with high density of nodes. Through the study of the main goals of data communication and the state of the art on the routing protocols and technologies for WSN, this proposal has the following requirements throughput, reliability on data delivery and energy-efficiency. The study presents in detail the AODV (Ad hoc On Demand Distance Vector) protocol and its relevance in the context of WSN, due to the fact of its popularity among the devices. Additionally, it is presented the proposed extensions for AODV and their main drawbacks to provide the required goals. The REL (Routing by Link Energy and Quality) protocol is the result of this research and the proposed solution for on-demand routing protocol for plan architecture based on energy-efficiency and link quality, in order to provide scalability, load balancing and prolong the network lifetime. The REL protocol was evaluated by using simulation and tesbed experiments in order to show its impact and benefits in real and simulated scenarios. The results presents that REL increases the data delivery rate due to the use of reliable links with less probability of error. Additionally, it uses energy issues to select routes, which avoid the fast saturation of nodes and increase the network lifetime.